Microbial Community Behaviour in The Rhizosphere of Kilemo (Litsea cubeba L. Pers) After Pruning - Widyati, Enny (Jurnal Manajemen Hutan Tropika, 2016)
Pruning is a removing some parts of the tree canopy, either for improving tree shape or increasing shoot productivity. It can be implemented in yield management of commodities that are harvested its shoot biomass, such as tea or kilemo. This activity interferes plant growth, hence affect root secretion. Consequently, it alters soil microbe populations in the rhizosphere. This paper observes the impacts of pruning on fluctuation of root exudates (soil sugar) and rhizosphere communities of 2-years-old Kilemo (Litsea cubeba L. Pers.). Tree samples were pruned by removing shoots above the lowest branches. A month after cutting, trees were fertilized using three types of fertilizers: leaf, NPK, and organic fertilizer. As a control, there were non-fertilized treated trees. To observe the root exudation and microbes populations, 0−20 cm depth of soil at rhizospheres were collected from 10th, 30th, 60th and 90th day after pruning.  Samples were further analyzed for observing the amount of soil-sugar and microbes population, such as N-fixer, cellulose degrader, and phosphate solubilizer. Results show that Kilemo root drastically decreased their sugar exudation by 22% (10th day), 28% (30th day), 44% (60th day) and 70% (90th day), respectively. Therefore, those populations were significantly depleted.  Rhizosphere sugar can be improved by fertilization, however, the augmentation did not enhance the rhizosphere communities.